Faktor motivasi dalam mempengaruhi staf sokongan untuk melanjutkan pelajaran : satu kajian kes di Universiti Malaysia Sarawak - Asning, Anak Nebor. (Universiti Malaysia Sarawak (UNIMAS), 2003)
This study aims to identify the motivationfactors which influenced the support stafJto continue their study. The objectives ofthis study are to investigate the differences between selected demography factors (age and length of services) with continuing the study and to examine the relationship between motivation factors; i) the job factor, ii) compensation and benefit factor, iii) organization structure factor and iv) individual factor with continuing study. Questionnaires were used as the instrument to obtain feedback from respondents. The data was analyzed by using the Statistical Package for the Social Science (Wtndows) version 10.0. Frequency and percentage were used to analyze the variable of respondent's demography. One-way A NOVA analysis showed that the age and length ofservice factor has no Significant difference with continuing the study. Therefore, the first and second hypothesis which states that there is no significant between age and length of service factor with continuing the study were accepted. The Pearson Correlation test showed that three ofthe hypothesis got positive significant between continuing the study with the job factor ( r = 0.355*, p < 0.05), compensation and benefit Jactor (r = 0.398*, p < 0.05) and organization structure factor (r = 0.575**, p < 0.01). From the findings, it is concluded that the third, Jourth and fifth hypothesis which stated that there is no significant relationship between contilluing with three Jactor were rejected. Sixth hypothesis showed that there is no significant relationship between individual Jactor with continuing study (r = 0.137, p > 0.01/0.05). Therefore from this study, it can be concluded that the organization itself played the most important role to support their stafJ to continue theirs studies.